The framing of scientific domains: about UNISIST, domain analysis and art history. Issue 2 (2014) - ,
Abstract : Purpose – By using the UNISIST models this paper argues for the necessity of domain analysis in order to qualify scientific information seeking. The models allow better understanding of communication processes in a scientific domain and they embrace the point that domains are always both unstable over time, and changeable, according to the specific perspective. This understanding is even more important today as numerous digitally generated information tools as well as collaborative and interdisciplinary research are blurring the domain borders. Nevertheless, researchers navigate "intuitively" in "their" specific domains, and UNISIST helps understanding this navigation. The paper aims to discuss these issues.Design/methodology/approach – The UNISIST models are tentatively applied to the domain of art history at three stages, respectively two modern, partially overlapping domains, as well as an outline of an art historical domain anno c1820. The juxtapositions are discussed against the backdrop of, among others, poststructuralist concepts such as "power" and "anti‐essentialism"Findings – The juxtapositions affirm the point already surfacing in the different versions of the UNISIST model, that is, structures of communication change over time as well as according to the agents that are charting them. As such, power in a Foucauldian sense is unavoidable in outlining a domain.Originality/value – The UNISIST models are applied to the domain of art history and the article discusses the instability of a scientific domain as well as, at the same time, the significance of framing a domain; an implication which is often neglected in scientific information seeking.